The Evolution of the Concept of Caliphate in Islamic Political History: Case Studies from Classical to Contemporary Times - Wijaya Wijaya; Faisal Razak; Nurul Huda (Yayasan Adra Karima Hubbi, 2024)
The concept of the caliphate has played a central role in Islamic political history, evolving significantly from the early classical period to contemporary times. Throughout Islamic history, the notion of the caliphate has shifted, reflecting the political, social, and cultural contexts of different eras. This evolution has sparked debate and differing interpretations among scholars, political leaders, and communities across the Muslim world. This study aims to explore the evolution of the concept of the caliphate, analyzing key case studies from classical Islamic history through to contemporary movements. The research seeks to understand how the concept has transformed over time and how these changes have influenced political thought in the Muslim world. The research utilizes a historical comparative approach, examining primary texts, political documents, and scholarly interpretations of the caliphate across different time periods. Case studies include the early Rashidun Caliphate, the Abbasid Caliphate, the Ottoman Caliphate, and modern interpretations by groups such as ISIS. A combination of qualitative content analysis and historical contextualization was applied. The study reveals that the concept of the caliphate has undergone significant ideological transformations, moving from a unifying political and religious institution in the classical period to more fragmented and symbolic representations in the modern era. Contemporary movements have reinterpreted the caliphate for political purposes, often deviating from classical principles. The evolution of the caliphate reflects broader changes in Islamic political thought, adapting to different historical and cultural contexts. This research highlights the complexity and diversity of interpretations surrounding the caliphate, emphasizing the need for nuanced understanding in contemporary discussions.